Development and Performance evaluation of Daylight Duct System with Multiple Light Distribution Modules - Lee, Heangwoo; Jang, Hyang-In; Choi, Chang-ho (International Journal of Engineering and Technology, 2019)
Recently, the consumption of energy in buildings for lighting purposes has been on the rise, which has led to an increase in research to find solutions to this issue. In this area of research, daylight ducts have been recognized for their efficiency as natural lighting systems, and have been the subject of various studies. Despite this, daylight ducts are limited in terms of their ability to improve upon lighting performance due to their application of single light distribution modules. Considering this, this research proposed a daylight duct system with multiple light distribution modules, and subjected the system to a performance evaluation to validate its effectiveness. To undertake the performance evaluation in this study, the light environment simulation program known as Radiance was used, and the conclusions of the evaluation were as follows. 1) The daylight duct system with multiple light distribution modules of this study included openings within the light distribution modules. The purpose of this method is to make it possible to open the openings of zones in which an influx of natural light was desired in order to let light into the zones. Through this approach, the system improves upon existing daylight duct systems in which light can enter only through fixed locations, thus increasing its efficiency. 2) The daylight duct system with multiple light distribution modules proposed in this study (Case 3) showed up to a 6.1% enhancement of average indoor light intensities compared to a system without light distribution modules (Case 1) and a system with a single light distribution module (Case 2). 3) The daylight duct system with multiple light distribution modules is capable of having the location of its light distribution modules adjusted to increase the uniformity of light distribution indoors. According to the settings of this study, it was found that the system can improve the uniformity of light distribution by 1.0%. In the future, continued efforts should be made to validate additional performance enhancements of the daylight duct system by diversifying indoor and outdoor parameters and the specifications of the daylight duct system, in addition to taking the parameters reviewed in this study into account.Â